PERCEIVED STRESS LEVEL AMONG MEDICAL STUDENTS - Shafiq Ur Rahman; Ameer Afzal Khan; Rahman Syed; Waqar Ahmad; Hamayun Khan; Ishaq Ahmad; Muhammad Dawood (Journal of Pakistan Psychiatric Society, 2025)
ABSTRACT Objective To assess perceived stress levels among medical students and identify key stressors. Study design Cross sectional study design was used. Place and duration of study The study was conducted in Saidu Medical College over a period of 3 months from 10 May to 11 August 2024. Subjects and Methods This quantitative, descriptive study enrolled students who consented for participation, while non-consenting were excluded. A self-administered questionnaire was used to gather data, which included demographic inquiries and the Perceived Stress Scale (PSS-14). Means for continuous parameters and frequencies for categorical parameters were used for analysis. Results Out of 180 students, 150 completed questionnaires. The sample included 61 females (40.6%) and 89 males (59.4%). Most respondents were boarders (72.6%) and single (93.3%). Stress levels revealed 24 students (16%) with low stress, 37 (24.6%) with moderate stress, and 89 (59.3%) with high stress. Males reported 23.6% low, 23.6% moderate, and 52.8% high stress, while females reported 28.26% low, 18.03% moderate, and 53.69% high stress. First-year students had the lowest stress, while final-year students experienced the highest overall stress. Conclusion The study concludes that medical students, especially those in their last year, report high levels of stress, with substantial gender differences. These results highlight the necessity of focused treatments to improve the wellbeing of students and deal with particular pressures in medical school. Key words Perceived Stress, Medical Students, Stress Level